Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan PT Bumi Asri Pasaman - Esqi Kurota Ayuni; Irwin Ananta Vidada (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The performance of an employee is the ability of each employee to perform the tasks assigned to them. Employee performance can affect the stability of the business. Where good employee performance affects the performance of the company. So, companies should pay attention to things that can improve employee performance like work environment and work motivation. This study aims (1) to determine the effect of work environment on employee performance of PT Bumi Asri Pasaman (2) to determine the effect of work motivation on employee performance of PT Bumi Asri Pasaman (3) to determine the effect of work environment and work motivation on employee performance of PT Bumi Asri Pasaman. This study aims (1) to determine the effect of work environment on employee performance of PT Bumi Asri Pasaman (2) to determine the effect of work motivation on employee performance of PT Bumi Asri Pasaman (3) to determine the effect of work environment and work motivation on employee performance of PT Bumi Asri Pasaman. This study uses a quantitative approach method with a sample population of 47 people. The sampling technique uses saturated samples, there are 47 respondents in this study. The data analysis method used is instrument test, test, classical assumptions, multiple linear regression test and hypothesis testing. The results of the research work environment and work motivation have a positive and significant influence on employee performance. The work environment and motivation together have a significant influence simultaneously on employee performance. While the results of the calculation of the coefficient of determination (R²) are known to be 0.419 or 41.9%, which means that the influence of the work environment and work motivation on employee performance is only 41.9% while the remaining 58.1% can be influenced by other variables not explained in the study.